The Introduction of World-Class Good Governance Ethics For Better Corporate Performance In Public-Listed Companies - Wan Ahmad Fauzi, Wan Husain; Siti Aisyah, Ahmad Zailani; Mohamad Reeduan, Mustapha (2022)
Ethics among managers, executives, and members of the board of directors working in public-listed companies brings grave concern due to the increasing number of criminal acts reported by the Security Commission of Malaysia. This study introduces a world-class good governance ethics framework for curbing criminal acts in public-listed companies. A qualitative case study using ethical analysis methodology is applied to meet its research objectives. It aims to promote world-class good governance ethics in curbing criminal acts for better corporate performance. The finding of this study reveals a world-class governance ethics framework as a means to improve individual integrity and corporate performance and a matter of choice, to adopt world-class good governance ethics in policies and practices of public-listed companies.